Geopolymer Concrete-Sustainable Cementless Concrete - Lloyd, Natalie; Rangan, Vijaya (American Concrete Institute, 2009)
Geopolymer is a specialized material resulting from the reaction of a source material that is rich in silica and alumina with alkaline solution. It is essentially portland cement free concrete. This material is being studied extensively and shows promise as a greener alternative to normal portland cement concrete. It has been found that geopolymer concrete has good engineering properties with a reduced carbon footprint resulting from the total replacement of normal portland cement. The research undertaken at Curtin University of Technology has included studies on geopolymer concrete mixture proportions, structural behaviour, and durability. This paper presents the results on mixture proportions development to enhance workability and strength of geopolymer concrete. The influence of factors such as: curing temperature and régime, aggregate shape, strength, moisture content, preparation and grading, and the addition of superplasticizers, on workability and strength are presented.